Transphobic victimisation and perceptions of future risk: a large-scale study of the experiences of trans people in the UK. Issue 3 (2nd July 2016) - Ellis, Sonja J.; Bailey, Louis; McNeil, Jay
Abstract : Due to perceived non-conformity to conventional constructions of gender, trans people may be subject to overt victimisation (e.g. physical or sexual violence; verbal abuse) and as a result of those experiences (actual or 'witnessed') may fear future victimisation. While some existing works report levels of transphobic victimisation, there is a dearth of research on perceived risk; and more importantly, exploring group differences in actual victimisation and perceived risk. Drawing on survey responses from 660 trans people, the current study sets out to explore levels of victimisation, perceived risk of victimisation, and group differences (gender identity; stage of transition) in both these phenomena. Findings show that congruent with work on systematic oppression and minority stress, perceived risk of victimisation outstrips actual experiences. Almost no group differences were found on a basis of gender identity. Conversely, those currently undergoing a process (or part of a process) of gender reassignment or transition were significantly more likely to report having been victimised, and to perceive themselves at risk of future victimisation than those at any other stage of transition. That levels of perceived risk outstripped actual experiences of victimisation suggests that, in a culture that privileges cis-gender experiences, isolated experiences of victimisation invoke a heightened sense of fear in members of the wider trans community. These findings suggest that there is a pressing need for dedicated support services for trans people; especially those who are going through a process of transitioning.